Demography vs. Context: A Cross-Country Survey of the Willingness to Rely on Trust in Business Partnerships - Francis Bidault; José R. de la Torre; Stelios H. Zanakis (European School of Management and Technology (ESMT), 2009)
We explore the determinants of the willingness to rely on trust in a business partnership where both partners are at risk. By focusing on the willingness to rely on trust (WTRT) we reduce the methodological challenge of perception-based approaches where trust is measured as an expectation on the partner's behavior. Executives in several countries were presented with a proposal for a business partnership and were asked about the level of safeguards they would require in the agreement, their main concerns as to future conditions, and to what extent their views would be affected by several behaviors and/or events. Twelve hypotheses are tested using path analysis and multiple/hierarchical regressions. Whereas our findings confirm prior results on differences in the propensity to trust between nationalities, they suggest that several organizational, functional and contextual variables mediate their impact in determining WTRT in inter-organizational ventures. Among these are the partners' cultural proximity, their concerns about business risk, and two organizational demographics regarding the size of the organization. In addition, we found that sensitivity to external information on partner's benevolence and the respondent's education and industry affected WTRT significantly.
urn:nbn:de:101:1-201106143618
Keywords: M16; 650; inter-organizational trust; willingness to rely on trust; trustworthiness; contractual safeguards; international joint ventures; business partnerships; international business; Lieferantenmanagement; Internationale Unternehmenskooperation; Vertrauen; Kulturelle Identität; Verhalten in Organisationen